Media framing of a political personality: a case study of a Malaysian politician - Lee, Kuok Tiung; Mohd Safar Hasim (EuroJournals, Inc., 2009)
The objective of this paper is to show how newspapers mould the image, personality and reputation of politicians through the pages of the newspapers by playing up or playing down their news and pictures. Using the framing theory, this paper looks at how 11 national and provincial newspapers frame news of Datuk Yong Teck Lee1, a politician from Sabah, a state within the Malaysian Federation. News samples were collected from 18 June 2008 (the day after the announcement made by Datuk Yong Teck Lee to quit the Coalition to the day after Coalition announced that they will focus on a Parliamentary by-election of Pematang Pauh on 7 August 2008. A total of 241 news and articles in Malay, English, and Mandarin were analyzed. In general, the study found mainstream and provincial newspapers differed in their reporting. Some newspapers tended to portray Datuk Yong Teck Lee negatively, while others pictured him as the hero of Sabah. There are also ‘neutral’ or objective reports. As the perception of people can be developed through their exposure of newspaper coverage, framing of news can help to show how newspapers play up or down such news and at the same time develop or destroy the reputation of political personalities.